Molecular investigation of mechanisms considered to cause preterm premature membrane rupture - Demir, Süleyman Cansun; Arslan, Erol; Ilgaz, Nermin Seda; Öksuz, Hale; Özpak, Lütfiye; Yılmaz, Mehmet Bertan; Akçabay, Çiğdem (Cukurova University, 2022)
Purpose: The aim of this study was to investigate the mRNA expression level of p16, CDK4, CDK6, Cyclin D, RB1, and E2F genes in preterm premature rupture of membrane (PPROM) cases and their roles in etiopathogenesis of PPROM.Materials and Methods: Twenty-one pregnancies with PPROM before 34th gestational weeks (study group) were compared with twenty pregnancies with no complication, who gave birth after 37th gestational-week (control group). Both groups chorioamniotic membranes were compared for mRNA expression of p16, cyclin D, CDK4, CDK6, RB1 and E2F genes.Results: The mRNA expression levels of p16, cyclin D, CDK4, CDK6, RB1and E2F genes decreased in the PPROM group compared to control group at a statistically significant level.Conclusion: Our findings have shown that oxidative stress may not act on the p16 pathway in these cases. In order to understand the molecular mechanism of PPROM, biomarkers of oxidative stress and aging should be evaluated together with other pathways related to aging and oxidative stress in future studies.

Amaç: Bu çalışmanın amacı, preterm erken membran rüptürü (PEMR) vakalarında, p16 ile CDK4, CDK6, siklin D, RB1, E2F genlerinin mRNA ekspresyon seviyelerini ve bu genlerin etiyopatogenezdeki rollerini saptamaktır. Gereç ve Yöntem: Çalışmamızda 34. gebelik haftasından önce membran rüptürü olan 21 gebe (çalışma grubu) ile herhangi bir durumla komplike olmamış ve 37. gebelik haftasından sonra doğum yapmış 20 gebenin (kontrol) doğum sonu koryoamniyotik membranları incelendi ve bu iki grubun koryoamniyotik membran örnekleri p16, siklin D, CDK4, CDK6, RB1 ve E2F genlerinin mRNA ekspresyon seviyeleri açısından karşılaştırıldı. Bulgular: Çalışmamızda, kontrol grubu ile kıyaslandığında p16, siklin D, CDK4, CDK6, RB1 ve E2F genlerinin ekspresyon seviyelerinin PEMR grubunda anlamlı derecede azaldığı saptandı. Sonuç: Bulgularımız bu vakalarda oksidatif stresin p16 yolağı üzerinden etki etmeyebileceğini göstermiştir. PEMR’nin moleküler mekanizmasını anlamak için, gelecekteki çalışmalarda oksidatif stres ve yaşlanma biyobelirteçleri ile yaşlanma ve oksidatif streste görevli diğer yolaklar birlikte değerlendirilmelidir.
Keywords: PPROM; P16; Cyclin D; CDK4; CDK6; RB1; E2F; PEMR; P16; Siklin D; CDK4; CDK6; RB1; E2F